Report of Meeting. The Seventh Katowice–Debrecen Winter Seminaron Functional Equations and Inequalities January 31 – February 2, 2007 Będlewo, Poland - AMSil, Redakcja (Annales Mathematicae Silesianae, 2007)
Report of Meeting. The Seventh Katowice–Debrecen Winter Seminaron Functional Equations and Inequalities January 31 – February 2, 2007 Będlewo, Poland.